Handbook of Ecotoxicology, Second Edition - Hoffman, David J (CRC Press, 2009)
Handbook of Ecotoxicology, Second Edition focuses on toxic substances and how they effect ecosystems worldwide. It presents methods for quantifying and measuring ecotoxicological effects in the field and in the lab, as well as methods for estimating, predicting, and modeling in ecotoxicology studies.